KEPENTINGAN UKRAINA MENERAPKAN KEBIJAKAN MORATORIUM EKSPOR KAYU MENTAH TAHUN 2015 - Indrayanthi, Luh Denia; Kawitri Resen, Putu Titah; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT This research aims to describe the interest of Ukraine in implementing moratorium on raw timber export policy in 2015 by using a qualitative research method. This research uses the benign mercantilism framework which explains the tendency of states regulating economic activities and policies to achieve their interests, including by applying protection in trade. Ukraine, which relies on natural resource wealth as the source of country’s economy, has also adopted this protectionism practice in the timber industry sector. The Ukrainian timber industry has been producing more unfavorable raw wood products. Ukraine then implemented a protectionism policy which was reflected in the Moratorium on Raw Wood Export policies. This research concludes that Ukraine's interest in implementing a moratorium on raw wood exports is to obtain maximum trade profits by encouraging the development of its domestic wood industry in producing value-added wood products. Keywords: Ukraine, Benign Mercantilism, Protectionism, National Interest, Trade Policy, Export Moratorium, Timber Industry